2016
DOI: 10.1002/lt.24458
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density predicts posttransplant survival among hepatocellular carcinoma liver transplant recipients

Abstract: Hepatocellular carcinoma (HCC) is a common indication for liver transplantation (LT). Recent data suggest that body composition features strongly affect post-LT mortality. We examined the impact of body composition on post-LT mortality in patients with HCC. Methods: Data on adult LT recipients who received MELD exception for HCC between 2/29/02-12/31/13 and had CT scan anytime 6 months prior to LT were reviewed (N=118). All available CT scan DICOM (Digital Imaging and Communications in Medicine) files were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
88
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 33 publications
5
88
3
Order By: Relevance
“…In this study, we used CT scan and analytic morphomics, which allow us to provide precise and detailed measurements of fat in liver, visceral, subcutaneous, and other body compartments such as muscles. We have previously shown that analytic morphomics measurements are accurate predictors of new‐onset diabetes and survival after liver transplantation, and provide important information about clinical outcomes in patients with liver disease …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used CT scan and analytic morphomics, which allow us to provide precise and detailed measurements of fat in liver, visceral, subcutaneous, and other body compartments such as muscles. We have previously shown that analytic morphomics measurements are accurate predictors of new‐onset diabetes and survival after liver transplantation, and provide important information about clinical outcomes in patients with liver disease …”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that analytic morphomics measurements are accurate predictors of new-onset diabetes and survival after liver transplantation, (24,27) and provide important information about clinical outcomes in patients with liver disease. (25,(41)(42)(43) Several studies have shown that ectopic fat deposition in the liver, skeletal muscle, and heart is a key determinant of insulin resistance. Adipose tissue is not only a site for storage of lipids, but it also secretes various hormones and cytokines involved in regulating glucose and lipid metabolism and energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Fractures of the vertebrae and hip may have an especially detrimental effect on physical function and HRQOL . In addition, it has been suggested that BMD may influence the postoperative outcomes of liver transplantation in patients with HCC . Therefore, evaluation of patients with chronic liver disease for sarcopenia and osteoporosis may improve their postoperative prognosis and prevent the reduction of HRQOL and ADL, which are related to the healthy lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55][56] In addition, it has been suggested that BMD may influence the postoperative outcomes of liver transplantation in patients with HCC. 57 Therefore, evaluation of patients with chronic liver disease for sarcopenia and osteoporosis may improve their postoperative prognosis and prevent the reduction of HRQOL and ADL, which are related to the healthy lifespan. Furthermore, the low SMI group showed a significant decrease in PeakVO 2 , which is an index of exercise tolerance reflecting overall endurance.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from AFP level and MVI, sarcopenia was identified as an independent and significant promoter of HCC relapse. In series of 118 HCC LT patients, Sharma et al [74] were able to demonstrate that bone mineral density (BMD), an early predictor of sarcopenia, is an independent predictor of post-LT mortality, with HCC recurrence to be the most common cause of death. A recent metaanalysis by Chang et al [75] including 13 studies and 3111 HCC patients after curative treatments concluded that sarcopenia is correlated with both, all-cause mortality (HR = 1.95; 95%CI 1.6-2.37) and tumor recurrence (HR = 1.76; 95%CI 1.27-2.45).…”
mentioning
confidence: 99%